2012
DOI: 10.1248/bpb.35.660
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Ethylacetate Extract of <i>Orostachys japonicus</i> on Induction of Apoptosis through the p53-Mediated Signaling Pathway in Human Gastric Cancer Cells

Abstract: Cancer rates are increasing dramatically, and there is currently a strong emphasis on identifying biologically active substances with anti-cancer activity from traditional herbs, as these are thought to have less adverse side-effects than conventional chemotherapy. Here, we examined the effects of extracts of Orostachys japonicus A. BERGER (O. japonicus) on cancer cell proliferation and apoptosis, and investigated the underlying signaling pathways. Dried powdered O. japonicus was extracted with 95% ethyl alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 20 publications
(25 reference statements)
2
29
1
2
Order By: Relevance
“…This fraction was analyzed using a GC‐MS system following the measurement methods detailed in our study. As a result, the following three peaks were identified: “gallic acid (4.24%), kaempferol (6.81%), and quercetin (5.08%)” (Lee et al., 2014; Ryu et al., 2012). Various studies have revealed that kaempferol and quercetin lead to apoptosis using the natural products in various human cancer cells (Lee, Szcsepanski, & Lee, 2008; Yoshida et al., 2008).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This fraction was analyzed using a GC‐MS system following the measurement methods detailed in our study. As a result, the following three peaks were identified: “gallic acid (4.24%), kaempferol (6.81%), and quercetin (5.08%)” (Lee et al., 2014; Ryu et al., 2012). Various studies have revealed that kaempferol and quercetin lead to apoptosis using the natural products in various human cancer cells (Lee, Szcsepanski, & Lee, 2008; Yoshida et al., 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Component analysis of the EtOAc fraction (OJE) has previously been described by our team (Lee et al., 2014; Ryu et al., 2012). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Orostachys japonicus A. Berger (Crassulaceae) (OJ), also known as Wa-song in Korea, is used as a folk medication; its main habitat is on the surface of mountain rocks in Korea and Japan. OJ is a medicinal plant with immunoregulatory, anti-febrile, antidote, and anticancer activities (Jin Kwon and Kwangsoo Han, 2004;Kim et al, 2011;Lee et al, 2011;Ryu et al, 2014;Ryu et al, 2012;Shin et al, 2013;Yoon et al, 2000). It is reported that OJ increased CD4-and CD8-T cells and the production of interferon γ in BALB/c mice (Jin Kwon and Kwangsoo Han, 2004).…”
Section: Introductionmentioning
confidence: 99%